Analisis Sistem Antrian Online Berbasis Simrs Di RSUD Al Ihsan - Salsa Nadila Rahmah, Denisa; Fitria, Ida Jalilah (Jurnal Online Manajemen ELPEI, 2025)
The SIMRS-based online queuing system is a health service innovation to overcome the problem of long and inefficient manual queues. This study aims to analyze the application of a SIMRS-based online queue system to the quality of service at Al Ihsan Hospital. The method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation to patients and medical personnel. The results of the study show that this system speeds up the enrollment process, reduces wait times, and improves patient satisfaction. However, obstacles such as limited user understanding and network interference were found that affected the effectiveness of the system. Therefore, increased socialization and technical optimization are needed. This research is expected to be a reference for other hospitals in the development of digital-based services to improve the quality of health services.